Local foods and markets support conservation of Garcinia fusca L. in Sisaket Province, Thailand - Hom, S.; Lamers, H.; Yoovatana, M.; Nimkingrat, T.; Somsri, S.; Sthapit, B. (2011)
This flyer describes one community’s success story of crop conservation. G. fusca, also known as madan, is used as a spice in India and as soup flavouring in Malaysia, but it was the Thai who discovered the most unique way of using the madan stem. A chicken is impaled on a madan stick and grilled over a fire, the madan gum secretes from the stick and mixes with the meat – giving it a distinctive flavour and aroma found nowhere else and making it a favorite among the locals. Due to the soaring popularity of the grilled chicken and the destruction of the madan’s natural habitat of the Tap Tan’s watershed, the plant species is now extremely vulnerable to overexploitation and local extinction. In order to protect their local grilled chicken industry and conserve the madan plants, the community has taken matters into their own hands and has made an effort to manage madan for the long term and for sustainable use.